Hubungan Kekuatan Otot Lengan Terhadap Keterampilan Servis Bawah pada Permainan Bola Voli Siswa SMK Negeri 3 Kota Kupang - Mone, Raimundus; Talan, Rudobertus; Liunokas, Oded; Ajito, Timoteus (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the relationship between arm muscle strength and underhand serving skills in volleyball among students at SMK Negeri 3 Kota Kupang. This study uses a quantitative approach with a correlational method. The study population consisted of 22 students who participated in volleyball extracurricular activities, and the entire population was sampled using total sampling technique. Data collection techniques were carried out through tests and measurements, namely push-up tests to measure arm muscle strength and standard volleyball underhand serve tests to measure students' underhand serve skills. The data obtained were analysed using Pearson Product Moment correlation analysis techniques after meeting the analysis prerequisites. The results showed a correlation coefficient of r = -0.222 with a significance value of p = 0.321 (p > 0.05). These findings indicate that there is no significant relationship between arm muscle strength and underhand serving skills in students at SMK Negeri 3 Kota Kupang. Thus, it can be concluded that underhand serving skills in volleyball are not only influenced by arm muscle strength but are more determined by other factors such as technical mastery, movement coordination, and timing in serving.